PAKET MENU MAKANAN KEMBUL BUJANA ( BANCAAN ) DI ERA GLOBALISASI SEBAGAI SARANA PELESTARIAN KULINER PENDIDIKAN KARAKTER - Sawitri Sawitri (p-ISSN 2356-0576, 2017)
ABSTRACT: Culture is inseparable from human beings creating fashion, art, house, vehicle and even food (meal). Diverse meals can be called culinary. Java has an unaccountable number of culinary products and forms from the sweet to the spicy and salty ones. Javanese people have culinary characterizing commonality and mutual cooperation (kegotongroyongan) by upholding local wisdom. Local areas have their own typical culinary. This article discussed Javanese typical culinary called kembul bujana often called bancaaan. Bancaan serves as the expression of gratitude to God. Bancaan is served for birth, syukuran, bersih desa, house establishment, job promotion, graduation, wedding or even reunion ceremonies, and etc. Kembul bujana is no longer held at house, yard, or ritual place. In globalization age, in fact, there is a cultural phenomenon in which the culture formerly considered as usual rite now is used for community’s practical purposes intended to economic factor. In this age, kembul bujana is used as the menu in restaurant and hotel, and those enjoying it come from upper middle class of society to billionaire. Its objective is different, no longer for rite purpose but emphasizing on uniqueness or art, and determining the position of package users and consumers such as socialite, rich employer, and urban people with well-established economy. Kembul bujana contains character education value that could be used as life tenets: commonality, mutual cooperation, not discriminating ethnic, race and religion, and tolerance. The life tenet teaches us that all human beings are equal before Almighty God, only his/her alms and goodness distinguish them.Keywords: Culture, package, meal, globalization age, character educationABSTRAK : Budaya tidak akan lepas dari manusia yang menciptakan dari pakaian, kesenian, rumah, kendaraan bahkan makanan. Makanan yang beraneka ragam dapat dikatakan kuliner. Jawa memiliki hasil dan bentuk kuliner dengan jumlah yang tidak terhitung dari selesa yang manis sampai pedas bahkan rasa gurih.Masyarakat Jawa mempunyai kuliner yang mencirikan kebersamaan bahkan kegotong royongan dengan menjunjung kearifan lokal. Daerah memiliki kuliner khas sendiri-sendiri. Diungkap dalam artikel ini merupakan kuliner khas Jawa berupa kembul bujana sering dikatakan bancaan. Fungsi bancaan pengucapan syukur kepada Tuhan. Bancaan untuk upacara kelahiran, syukuran, bersih desa, pendirian rumah, naik pangkat, kelulusan selesai kuliah, pernikahan bahkan reuni teman sekolah, teman kerja dll. Tempat diadakannya kembul bujana tidak lagi di rumah, di pelataran, tempat ritual. Pada era globalisasi ternyata ada fenomena budaya terjadinya perkembangan budaya yang awalnya dianggab hal biasa cenderung ritual sekarang untuk kebutuhan praktis masyarakat yang ditujukan untuk faktor ekonomi. Pada era sekarang kembul bujana digunakan untuk menu pada restoran, di hotel dan yang menikmati kalangan dari menengah sampai milyader. Tujuan juga berbeda tidak lagi ritual melainkan menitikberatkan segi keunikan atau seni. Menentukan posisi dari pengguna dan pengkomsumsi paket juga. Kaum sosialita, pengusaha kaya cenderung masyarakat kota dengan ekonomi mapan. Kembul bujana mengandung nilainilai pendidikan karakter yang dapat digunakan sebagai ajaran hidup, yaitu: pendidikan karakter kebersamaan, kegotong royongan, tidak membedakan suku, ras dan agama, toleransi. Ajaran hidup di hadapan Tuhan Yang Maha Esa manusia sama yang membedakan amal kebaikannya.Kata kunci: Budaya, paket, makanan, era globalisasi, pendidikan karakter